Analisis Pengaruh Corporate Social Responsibility Dan Reputasi Organisasional Terhadap Ketertarikan Organisasional - Handayani, Rini (STIE Surakarta, 2013)
Organizations that make the job seeker interested will bring a positive impact to the organization. Organizations will have the opportunity to get talented employees and have compatibility with the organization. Corporate Social Responsibility (CSR) and organizational reputation are several factors that can affect the organizational attractiveness.This study was conducted on 80 students of final semester at some private universities in the city of Semarang to test the perception of CSR and organization reputation of the organizational attractiveness. The tests performed with linear regression analysis with SPSS 17. However, to test the organizational reputation as a mediating variable between CSR and organizational attractiveness, path analysis was used.The results showed that a significant positive effect of CSR on organizational reputation and organizational attractiveness. Besides that, organizational reputation also showed a positive significant effect on organizational attractiveness. At the end of the analysis showed that organizational reputation turns out to mediate the relationship between CSR and organizational attractiveness